Kehidupan Survival Masyarakat Padang Pasir dalam Novel Wahat Al-Ghurub Karya Baha Taher (Perspektif Ekokritik Greg Garrard) - Nirmala, Bening Nuha; Surur, Misbahus (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2023)
Desert is an ecosystem that rarely receives attention in literary works. This study discusses the representation of life in the desert and potrays it’s survival aspects in the novel “Wahat Al-Ghurub” by Baha Taher. This research is descriptive qualitative. The data source used is the novel “Wahat Al-Ghurub” (Sunset Oasis) by Baha Taher. Data collection was done by reading and taking note technique. Data were analyzed using Miles & Huberman method, which consists of three stages: data reduction, data display, and conclusion drawing. This study aims to describe how the desert’s environtment and survival aspects are described in the novel. The results of this study show that the author portrays the desert as a harsh and empty land, yet with a beautiful landscape. The author also describes how the desert affects human life, both physically and psychologically. In particular, the potrayal of the survival methods of it’s society to continue life within the vast expanse of the desert. This research provides a fresh perspective on the lesser-known aspects of desert life potrayed through literary works.